The Association between Phencyclidine Use and Partner Violence: An Initial Examination - Crane, Cory A. (2013)
The association between phencyclidine (PCP) use and violent behavior is unclear. The present investigation evaluated the association between PCP addiction and intimate partner violence, a specific violent behavior, using the substance abuse evaluations of 109 PCP, 81 cannabis, and 97 polysubstance (alcohol and cannabis) abusing offenders. Relative to both comparison groups, PCP users were more likely to receive inpatient referrals, have a significant legal history, and have perpetrated past-year general and intimate partner violence. Data suggest that PCP use may be associated with greater violence perpetration than cannabis use alone or in conjunction with problematic alcohol use.